Aberrant expression of apoptosis proteins and ultrastructural aberrations in uterine leiomyomas from patients with hereditary leiomyomatosis and renal cell carcinoma. - Wortham, N; Alam, N; Barclay, E; Pollard, P; Wagner, B; Manek, S; Elia, G; Tomlinson, I (2006)
OBJECTIVE: To examine differences between sporadic and familial uterine leiomyomata related to expression of apoptosis-related proteins and tumor ultrastructure. DESIGN: Expression of apoptosis-related proteins was measured by immunohistochemistry. Tumor ultrastructure was evaluated by transmission electron microscopy. SETTING: Human genetics laboratory. PATIENT(S): Patients confirmed for hereditary leiomyomatosis and renal cell carcinoma (HLRCC), and anonymous archival sporadic leiomyoma patients. INTERVENTION(S): Samples for electron microscopy were collected from myomectomy and hysterectomy with informed consent. Other samples were archival. MAIN OUTCOME MEASURE(S): Intensity of immunohistochemistry staining and evaluation of electron micrographs. RESULT(S): Immunohistochemistry revealed increases in expression of antiapoptotic Bcl-2 and the proliferation factor proliferating cell nuclear antigen (PCNA) in both sporadic and HLRCC uterine leiomyomata. Furthermore, we observed an increase in antiapoptotic Bcl-x and a concurrent decrease in proapoptotic Bak solely in HLRCC leiomyomas. We also observed ultrastructural alterations in HLRCC and sporadic leiomyomas, particularly pertaining to extracellular matrix and intermediate filament aggregation. CONCLUSION(S): The observed alterations in expression of apoptosis-related proteins indicate a shift in both HLRCC and sporadic leiomyomas to increased resistance to apoptosis compared with myometrium, which appears to be stronger in HLRCC leiomyomas. The changes observed in HLRCC leiomyomas appear to be related to activation of the hypoxia pathways. The results suggest not only a partial overlap in the pathogenic mechanism of the two tumor types, but also intriguing differences.